Soft Tissue Reconstruction with Free Gingival Graft Technique following Excision of a Fibroma - Nurcan Tezci; Suleyman Emre Meseli; Burcu Karaduman; Serap Dogan; Sabri Hasan Meric (Case Reports in Dentistry)
Background. Oral fibromas are benign, asymptomatic, smooth surfaced, firm structured tumoral lesions that originate from gingival connective tissue or periodontal ligament. Histologically, they are nodular masses characterized by a dense connective tissue, surrounded by stratified squamous epithelium. Case Report. This case report includes the clinical, radiographical, and histological findings and periodontal treatment of a 38-year-old female patient having painless swelling on the gingiva. Intraoral examination revealed a fibrotic, sessile, smooth surfaced gingival overgrowth interdentally between the teeth #13 and #14. Radiographical findings were normal. Initial periodontal treatment (IPT) was applied including oral hygiene instructions, scaling, and root planing. Following IPT, the lesion (0.7 × 0.6 × 0.4 cm) was excised and examined histopathologically. Subsequently, flap operation was performed to have an access to alveolar bone. Surgical site was reconstructed with free gingival graft obtained from hard palate. Hematoxylin-eosin stained sections revealed a nodular mass composed by dense collagen fibers in lamina propria covered by a stratified squamous epithelium, which were consistent with fibroma. Gingival healing was uneventful and without any recurrence during the 12-month follow-up. Conclusions. In order to achieve optimal functional and aesthetical outcomes, free gingival graft can be used for the reconstruction of the wound site after the excision of the fibroma.